Lack of association of the CEP72 rs924607 TT genotype with vincristine-related peripheral neuropathy during the early phase of pediatric acute lymphoblastic leukemia treatment in a Spanish population. Issue 2 (February 2016) - Gutierrez-Camino, Angela; Martin-Guerrero, Idoia; Lopez-Lopez, Elixabet; Echebarria-Barona, Aizpea; Zabalza, Iñaki; Ruiz, Irune; Guerra-Merino, Isabel; Garcia-Orad, Africa
Abstract : Vincristine is a component of acute lymphoblastic leukemia (ALL) treatment with the potential to induce peripheral neuropathy. Recently, the CEP72 rs924607 TT genotype was found to be associated with vincristine-induced toxicity during the continuation phase in pediatric ALL patients treated on the Total XIIIB and COG AALL0433 protocols at St Jude Children's Research Hospital and Children's Oncology Group. This finding could provide a base for safer dosing of vincristine. Nevertheless, there are variations in vincristine regimens among ALL treatment protocols and phases in different populations. Therefore, the aim of this study was to determine whether the CEP72 rs924607 TT genotype is a useful marker of vincristine neuropathy during induction therapy among Spanish children with B-ALL treated on the LAL-SHOP protocols. No association was found between neurotoxicity during the induction phase and the rs924607 TT genotype. This lack of association could be because of population differences and/or differences in neurotoxicity etiology between induction and continuation phases of treatment.